Toward Platform-Economy Continuity: Do Descriptive Norms and Perceived Product Attributes Matter to Youths who Use Ride-Hailing Apps? - Fauzi, Abu Amar (The Asian Journal of Technology Management (AJTM), 2022)
Abstract. This study investigates how descriptive norms and perceived product attributes (utilitarian and hedonic benefits) influence the intention of young consumers to continue to adopt ride-hailing apps. We developed a conceptual model drawing upon the socio-technical theory by involving 333 Indonesian users of ride-hailing apps and estimating the model using the statistical tool of PLS-SEM-based software. The findings showed that social aspects (descriptive norms) and technical aspects (utilitarian and hedonic benefits) significantly influence young consumers to adopt ride-hailing apps. Intriguingly, a positive perception of the apps’ benefits is instrumental for encouraging young consumers to continue to adopt ride-hailing apps when descriptive norms appear, when peers in their social circle widely adopt similar apps. This study highlights the unique behavior of young consumers in adopting ride-hailing apps by accentuating the role of descriptive norms and perceived product attributes from the perspective of socio-technical theory. This study provides practical recommendations for digital platform providers, particularly TNCs (Transportation Network Companies), which offer ride-hailing services to address the young consumer segment with a community-based marketing approach to maintain their continued adoption.   Keywords: Continuation intention, platform economy, digital platform, ride-hailing services, socio-technical theory, young consumers